Urgensi Pendidikan Tauhid dalam Keluarga - Muhtadi Muhtadi (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This study aims to describe the concept of tawheed education which is still urgent to be applied in families at this time, as a knowledge discourse to foster children's faith. This research is a library research, on previous works, with a qualitative descriptive approach. The data collection technique is documentation technique, while the data analysis uses content analysis technique. The results of the study indicate that the concept of tawheed education is a conceptual framework that contains ideas, descriptions, understandings, and thoughts about tawheed education materials and methods that can foster faith in the oneness of Allah SWT. The concept of tawheed education remains urgent to be applied in the family, so that families, especially children, truly believe in the oneness of Allah SWT, in order to achieve the happiness of life in this world and the hereafter.